A Turn‐On Sensor for Highly Sensitive and Selective Detect Heparin in Human Serum Albumin. Issue 15 (19th April 2022) - Huang, Cuiping; Cao, Jian; Liu, Mingming; Tu, Yajing; Zhang, Meijuan; Zheng, Junying
Abstract: A novel positively charged sensor, NAP ‐MBT +, was designed and constructed by introducing a 2‐methylbenzothiazole cation (MBT + ) into naphthalimide derivative (NAP ‐phCHO ) via a double carbon bond. NAP ‐MBT + can realize the detection sensitively and selectively for heparin (Hep) by "turn‐on" fluorescence emission in several seconds. NAP ‐MBT + displayed the very significant fluorescence emission enhancement only to Hep among various interference from counter ions and biomolecules. The fluorescence emission of NAP ‐MBT + to Hep depended on the electrostatic attraction between the positive and negative charges. NAP ‐MBT + ‐Hep assembly can be dissociated by protamine (PRTM) appearing an "off‐on‐off" signal because of the stronger affinity of Hep to PRTM. NAP ‐MBT + was successfully applied to detect Hep in 0.2 % human serum. Abstract : Hep (heparin) with the negative charge had a suitable electrostatic adsorption with the positively charged NAP ‐MBT + (sensor), and inducing a fluorescence emission enhancement of sensor. PRTM (protamine) could disaggregate NAP ‐MBT + ‐Hep complex, leading to a fluorescence quenching.